2017
DOI: 10.1016/j.socscimed.2017.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Rationing hepatitis C treatment in the context of austerity policies in France and Cameroon: A transnational perspective on the pharmaceuticalization of healthcare systems

Abstract: New powerful drugs against hepatitis C can cure the disease, but they are not widely distributed because their exorbitant prices are destabilizing healthcare systems in both African and European countries. This article takes access to hepatitis C treatments since 2013 in France and in Cameroon as a lens to analyze the rationing of pharmaceutical treatments in relation to recent transformations of health systems. Access to these treatments is analyzed thanks to ethnographic observation and interviews lead in Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Our study corroborates the results of other studies in sub-Saharan Africa pointing to serious patient destabilisation associated with HBV diagnosis, inability to pay for medical care and feelings of injustice 11. However, the impact of HBV and HCV on life trajectories have rarely been documented in qualitative studies, which mainly focus on patients’ representations and experiences of HBV infection,11 on obstacles to linkage to care after diagnosis of HBV12 and on access to HCV treatment 10. In line with studies on linkage to care,4 12 we identified large barriers for patients diagnosed with HBV or HCV, mainly at the structural level, including (i) a lack of adequate training of HCP which resulted in frequent misconceptions about transmission, natural history and diagnosis, (ii) a lack of simple, reliable and low-cost diagnostic tests and (iii) a lack of funding allocated to the fight against hepatitis, which resulted in unaffordable user fees for prevention, care and treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study corroborates the results of other studies in sub-Saharan Africa pointing to serious patient destabilisation associated with HBV diagnosis, inability to pay for medical care and feelings of injustice 11. However, the impact of HBV and HCV on life trajectories have rarely been documented in qualitative studies, which mainly focus on patients’ representations and experiences of HBV infection,11 on obstacles to linkage to care after diagnosis of HBV12 and on access to HCV treatment 10. In line with studies on linkage to care,4 12 we identified large barriers for patients diagnosed with HBV or HCV, mainly at the structural level, including (i) a lack of adequate training of HCP which resulted in frequent misconceptions about transmission, natural history and diagnosis, (ii) a lack of simple, reliable and low-cost diagnostic tests and (iii) a lack of funding allocated to the fight against hepatitis, which resulted in unaffordable user fees for prevention, care and treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the complex challenges to sub-Saharan HCP, patients and health systems mentioned above, most of these challenges remain dramatically understudied. Comprehensive assessments of the circumstances and experiences of patients and HCP in terms of diagnosis, counselling and care for both diseases are sparse,10–12 especially in countries with poor access to related medical care. In this study, we aimed to document circumstances and perceptions surrounding HBV and HCV screening and counselling, and experiences with regard to access to care and treatment, and the impact these infections have on social and economic trajectories of patients in Yaoundé, the capital city of Cameroon.…”
Section: Introductionmentioning
confidence: 99%
“…Although considerable research has been conducted on politics and health in England to explain how politics is implicated in north-south health inequalities in England, 4 a paucity of research remains on politics and health in Ghana. The approach and rationale adopted in our review is similar to Chabrol et al, 92 who use France and Cameroon to demonstrate the "pharmaceuticalization of health systems" in the context of austerity policies. Such comparisons of distinct settings are useful, as they show the specific contextually situated and historically relevant factors necessary for responding to the challenge of health inequities in different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, global health hierarchically organizes disease categories by their urgency for human economic and physical vitality at a global scale (World Bank 1993). This categorization and prioritization is triage, and though triage in Europe and North America is largely confined to emergency care, austerity policies propagate forms of triage also in nonemergency settings in medical systems there, too (Kentikelenis 2015;Chabrol, David, and Krikorian 2017).…”
Section: Speculative Imaginariesmentioning
confidence: 99%